Typology of Tahfidz Islamic Boarding School Curriculum in South Kalimantan - Rasyidi, Ahyar; Setiawan, Agus (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
The purpose of this research is to describe the typology of the curriculum of tahfizh boarding schools in South Kalimantan. Curriculum as a guideline in learning at an educational institution, especially the tahfizd pesantren educational institution, has not been widely existed and researched so it is interesting to research. The method used is a qualitative method. Data analysis techniques that will be used in this research, namely